High-temperature and high-pressure resistant intelligent self-repairing anticorrosive coating, preparation method and application thereof

CN123004237APending Publication Date: 2026-10-30XIAN THERMAL POWER RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611306786.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-26
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]为了克服上述现有技术的缺点,本发明的目的在于提供一种耐高温高压智能自修复防腐涂层及其制备方法和应用,用以解决现有技术中核电防腐涂层无法同时耐受高温高压极端工况并具备损伤后自主快速修复功能的技术问题

Benefits of technology

本发明提供一种耐高温高压智能自修复防腐涂层的制备方法,首先,在基材预处理阶段采用低温等离子体进行表面活化处理,相较于传统仅依靠喷砂粗化的方式,可显著提升基材表面能并引入活性官能团,使后续涂层与基材的结合强度提升至45MPa以上,有效解决了长期服役过程中涂层易分层剥落的技术难题;其次,在复合成膜基体配制阶段将耐高温改性环氧树脂与有机硅改性聚氨酯复配,结合聚四氟乙烯微粉的增韧作用,使成膜基体兼具高交联密度与优异的抗热氧老化性能,配合后续的分段梯度升温固化工艺,可有效消除涂层内部应力集中和溶剂残留气孔,使涂层致密度大幅提升、孔隙率降至0.8%以下;在此致密化基础上,分段梯度升温固化工艺还协同保护了包覆于涂层内部的温度/应力双响应微胶囊,避免其因高温急剧固化而提前破裂失活,确保微胶囊在常温储存及常规施工过程中保持囊壁结构完整与芯材零泄漏,仅在涂层服役过程中遭遇温度≥250℃极端高温或微裂纹尖端应力≥0.5MPa的局部应力集中时,囊壁才按设计触发破裂并释放缓蚀剂芯材,实现对损伤区域的精准自主修复;此外,高熵合金纳米粉体协同纳米二氧化硅气凝胶和氧化铬构成的复配耐蚀体系,经硅烷偶联剂表面修饰后均匀分散于涂层中,在高温硼酸/海水腐蚀介质中可形成致密钝化阻挡层,进一步强化涂层的抗介质渗透与抗冲蚀能力。经上述多步骤协同作用,所制备涂层可在400℃、20MPa工况下连续服役500h无开裂脱落,微损伤后30min内完成自主修复,且整体工艺步骤简洁、参数可控、无需昂贵设备,具有良好的工业化规模施工前景。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a high-temperature and high-pressure resistant intelligent self-repairing anticorrosive coating and a preparation method and application thereof, and relates to the technical field of anticorrosive coatings for nuclear power equipment. The method comprises the following steps: performing low-temperature plasma activation treatment on a metal substrate, compounding a high-temperature resistant modified epoxy resin, a silicone modified polyurethane and polytetrafluoroethylene micropowder to form a film forming matrix, modifying high-entropy alloy nano-powder, silica aerogel and chromium oxide powder by a silane coupling agent to obtain a corrosion resistant filler, compounding a molybdate coated with urea-formaldehyde resin and an organic amine to obtain a double-response microcapsule, adding the filler and the microcapsule into the matrix to form a coating, and performing gradient spraying to form a primer layer, a middle coating layer and a top coating layer, and then performing sectional gradient temperature curing. The coating has a porosity of less than or equal to 0.8%, a bonding strength of greater than or equal to 45 MPa, can be used at 400 DEG C and 20 MPa for 500 hours without cracking and falling off, can be self-repaired within 30 minutes after micro-damage, and is suitable for the corrosion protection of key equipment of pressurized water reactors and fourth-generation reactors of nuclear power stations.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of anti-corrosion coating technology for nuclear power equipment, specifically relating to a high-temperature and high-pressure resistant intelligent self-healing anti-corrosion coating, its preparation method, and its application. Background Technology

[0002] Nuclear power equipment operates under extreme conditions of high temperature, high pressure, high humidity, and highly corrosive media for extended periods. Taking pressurized water reactor nuclear power plants as an example, the primary coolant system typically operates at temperatures of 280–350°C and pressures of 15–18 MPa, with the coolant containing corrosive media such as boric acid. Fourth-generation advanced nuclear energy systems, such as molten salt reactors and lead-cooled fast reactors, operate at temperatures exceeding 600°C, placing even higher demands on the high-temperature and corrosion resistance of equipment structural materials. Key metal components within the nuclear island, such as steam generator heat transfer tubes, main pipelines and welds, and the inner wall of the reactor pressure vessel, are highly susceptible to stress corrosion cracking (SCC), intergranular corrosion, pitting corrosion, and flow-accelerated corrosion in long-term high-temperature, high-pressure water environments, severely threatening the safe operation and service life of nuclear power units. Statistics show that corrosion-related failures account for over 40% of all nuclear power equipment failures, with stress corrosion failure being particularly prominent and becoming one of the key bottlenecks restricting the long-term safe operation of nuclear power equipment.

[0003] Currently, the main technical approaches adopted in engineering for corrosion protection of nuclear power equipment are as follows: one is to upgrade the alloy grade of the base material, such as using Inconel 690 alloy or Incoloy. Nickel-based corrosion-resistant alloys such as Alloy 800 are used, but this approach is extremely expensive and cannot completely eliminate stress corrosion. Secondly, cold spraying or supersonic flame spraying can be used to prepare metal / alloy protective coatings. While these coatings offer some corrosion resistance, they inevitably contain defects such as pores and microcracks, allowing corrosive media to penetrate along these defects to the substrate interface. Furthermore, the difference in thermal expansion coefficients between the metal coating and the substrate can easily lead to coating peeling during thermal cycling. More importantly, they lack any self-healing capabilities. Thirdly, traditional organic anti-corrosion coatings, such as epoxy resin and polyurethane systems, are used. While these coatings are easy to apply and moderately priced, their high-temperature resistance is generally insufficient. In environments above 200°C, they are prone to resin aging, thermal decomposition, powdering, and peeling, failing to meet the long-term high-temperature service requirements of nuclear power plants. Moreover, once the coating suffers micro-damage from external forces, it cannot self-repair, and the damaged area rapidly expands into macro-cracks, ultimately leading to the complete loss of the coating's protective function.

[0004] In recent years, self-healing smart coatings have become a research hotspot in the field of corrosion protection. However, most of the existing publicly available self-healing coating technologies are geared towards applications in normal temperature, normal pressure, and atmospheric environments. Their self-healing function usually relies on a single environmental stimulus response mechanism (such as a single light response, a single pH response, or a single moisture response). In the extreme environment of nuclear power plants with high temperature, high pressure, and multi-field coupling, conventional microcapsule wall materials are prone to premature rupture and failure, and corrosion inhibitor core materials are prone to decomposition and inactivation at high temperatures. The repair response speed is slow or even completely fails, making it impossible to achieve effective autonomous repair under nuclear power operating conditions. In addition, existing self-healing coatings generally suffer from insufficient coating density, low interfacial bonding strength with the metal substrate, and easy delamination and peeling after long-term service, making it difficult to meet the stringent requirements of nuclear power plants for a coating protection life of 40 to 60 years. Summary of the Invention

[0005] In order to overcome the shortcomings of the prior art, the present invention aims to provide a high-temperature and high-pressure resistant intelligent self-healing anti-corrosion coating, its preparation method and application, so as to solve the technical problem that the existing nuclear power anti-corrosion coating cannot simultaneously withstand the extreme working conditions of high temperature and high pressure and have the function of autonomous and rapid repair after damage.

[0006] To achieve the above objectives, the present invention employs the following technical solution: In a first aspect, the present invention provides a method for preparing a high-temperature and high-pressure resistant intelligent self-healing anti-corrosion coating, comprising the following steps: S1. The surface of the nuclear power metal substrate is pretreated, and then surface activation treatment is performed by low-temperature plasma to obtain the pretreated substrate. S2, a composite film-forming matrix is ​​prepared by mixing high-temperature resistant modified epoxy resin, organosilicon modified polyurethane, polytetrafluoroethylene micro powder, curing agent, dispersant, defoamer and anhydrous ethanol solvent, and then dispersing and homogenizing by stirring and ultrasonic treatment. S3, high-entropy alloy nanoparticles, nano-silica aerogels and nano-chromium oxide powders are mixed, and the surface is modified with a silane coupling agent. After drying and grinding, a modified corrosion-resistant filler is obtained. S4, using urea-formaldehyde resin as the capsule wall material, and coating it with a composite core material containing corrosion inhibitors and passivators, to prepare self-healing microcapsules; S5, the modified corrosion-resistant filler prepared in S3 and the self-healing microcapsules prepared in S4 are added to the composite film-forming matrix prepared in S2, and after stirring evenly and vacuum degassing treatment, an intelligent self-healing anti-corrosion coating is obtained. S6. Using a gradient spraying process, the intelligent self-healing anti-corrosion coating prepared in S5 is sequentially sprayed onto the surface of the pretreated substrate obtained in S1 to form a primer layer, a middle layer and a topcoat layer, respectively. After a segmented gradient temperature curing treatment, the high temperature and high pressure resistant intelligent self-healing anti-corrosion coating is obtained.

[0007] A further improvement of the present invention is that, in S1, the pretreatment includes sandblasting to remove rust, degreasing and cleaning, the sandblasting rust removal grade reaches Sa3.0, and the surface roughness of the substrate after sandblasting is 40~60μm; the low-temperature plasma surface activation treatment is carried out in an argon atmosphere, the treatment power is 300~400W, and the treatment time is 5~9min.

[0008] A further improvement of the present invention is that, in S2, the high-temperature resistant modified epoxy resin is at least one of silicone modified epoxy resin, polyurethane modified epoxy resin, or phenolic modified epoxy resin; the curing agent is at least one of amine curing agent, phenolic curing agent, or acid anhydride curing agent; the dispersant is at least one of polyacrylate dispersant, polyurethane polymeric dispersant, amine / polyamide dispersant, or silicone dispersant; the defoamer is at least one of silicone defoamer, non-silicone polyether defoamer, or acrylate polymeric defoamer; the stirring and dispersion speed is 700~1000 r / min, and the stirring time is 30~40 min; the ultrasonic homogenization power is 200 W, and the time is 10~30 min.

[0009] A further improvement of the present invention is that, in S3, by mass parts, the high-entropy alloy nanopowder is 10-15 parts, the nano-silica aerogel is 3-7 parts, and the nano-chromium oxide powder is 2-4 parts; the high-entropy alloy nanopowder is FeCrAlTiMo high-entropy alloy nanopowder; the silane coupling agent is KH-560, the modification temperature is 60-70℃, the modification time is 1.5-3.5h, the drying temperature is 80℃, and the particle size of the modified corrosion-resistant filler after grinding is ≤100nm.

[0010] A further improvement of the present invention is that, in S4, the composite core material is composed of molybdate corrosion inhibitor and organic amine passivator in a mass ratio of 2:1; the wall thickness of the self-healing microcapsule is 30~50nm; and the self-healing microcapsule has a dual-response characteristic of triggering the release of the core material when the temperature is ≥250℃ and / or the coating microcrack stress is ≥0.5MPa.

[0011] A further improvement of the present invention is that, in S5, the amount of modified corrosion-resistant filler added is 12% to 18% of the total mass of the intelligent self-healing anti-corrosion coating; and the amount of self-healing microcapsules added is 4% to 9% of the total mass of the intelligent self-healing anti-corrosion coating.

[0012] A further improvement of the present invention is that, in S6, the coating thickness of the primer layer is 20~30μm, the coating thickness of the intermediate layer is 40~50μm, and the coating thickness of the topcoat layer is 30~40μm; the segmented gradient temperature curing treatment is as follows: surface drying at room temperature for 30min, pre-curing at 80℃ for 1h, curing at 150℃ for 2h, final curing at 220℃ for 3h, and then naturally cooling to room temperature.

[0013] Secondly, the present invention also provides a high-temperature and high-pressure resistant intelligent self-healing anti-corrosion coating, which is prepared by the preparation method described above.

[0014] A further improvement of the present invention is that the coating is a multi-layer composite structure with a total thickness of 90~120μm and a porosity of ≤0.8%. The bonding strength between the coating and the metal substrate is ≥45MPa. The coating can be continuously operated for 500 hours at a high temperature of 400℃ and a high pressure of 20MPa without cracking, peeling or powdering. Moreover, the coating surface can be self-repaired within 30 minutes after microcracks or shallow scratches occur.

[0015] Thirdly, the present invention also provides an application of the high-temperature and high-pressure intelligent self-healing anti-corrosion coating as described above in the corrosion protection of nuclear power equipment. The coating is used for corrosion protection of the primary loop pipeline, secondary loop pipeline, steam generator heat transfer tube, main pipeline weld, reactor pressure vessel inner wall, and high-temperature pressure-bearing equipment of fourth-generation molten salt reactor and lead-cooled fast reactor in nuclear power plants.

[0016] Compared with the prior art, the present invention has the following beneficial effects: This invention provides a method for preparing a high-temperature and high-pressure resistant intelligent self-healing anti-corrosion coating. First, in the substrate pretreatment stage, low-temperature plasma is used for surface activation treatment. Compared to the traditional method relying solely on sandblasting roughening, this significantly increases the surface energy of the substrate and introduces active functional groups, increasing the bonding strength between the coating and the substrate to over 45 MPa, effectively solving the technical problem of coating delamination and peeling during long-term service. Second, in the composite film-forming matrix formulation stage, high-temperature modified epoxy resin and silicone-modified polyurethane are compounded, combined with the toughening effect of polytetrafluoroethylene micropowder, giving the film-forming matrix both high crosslinking density and excellent resistance to thermo-oxidative aging. Combined with the subsequent segmented gradient temperature curing process, this effectively eliminates internal stress concentration and solvent residue pores in the coating, significantly increasing the coating density and reducing the porosity to below 0.8%. Based on this densification, the segmented gradient temperature curing process also synergistically protects the temperature / stress dual-response microcapsules encapsulated inside the coating, preventing them from prematurely rupturing and deactivating due to rapid curing at high temperatures. This ensures that the microcapsules maintain the integrity of their capsule wall structure and zero leakage of the core material during normal storage and conventional construction. Only when the coating encounters extreme high temperatures ≥250℃ or local stress concentrations ≥0.5MPa at the microcrack tip during service will the capsule wall trigger rupture as designed and release the corrosion inhibitor core material, achieving precise autonomous repair of the damaged area. In addition, the high-entropy alloy nanopowder, together with nano-silica aerogel and chromium oxide, forms a composite corrosion-resistant system. After surface modification with a silane coupling agent, it is uniformly dispersed in the coating. In high-temperature boric acid / seawater corrosive media, it can form a dense passivation barrier layer, further enhancing the coating's resistance to media penetration and erosion. Through the synergistic effect of the above multiple steps, the prepared coating can be continuously used for 500 hours without cracking or peeling under working conditions of 400℃ and 20MPa. It can also complete self-repair within 30 minutes after micro-damage. Moreover, the overall process steps are simple, the parameters are controllable, and no expensive equipment is required, which has good prospects for industrial-scale construction.

[0017] This invention also provides a high-temperature and high-pressure resistant intelligent self-healing anti-corrosion coating. Compared with existing nuclear power anti-corrosion coating products, it achieves significant breakthroughs in core performance indicators in terms of extreme operating condition tolerance and intelligent repair function: the coating-substrate bonding strength is ≥45MPa, the porosity is ≤0.8%, and it can withstand 400℃ high temperature and 20MPa high pressure for a long time and continuously operate for 500 hours without cracking or peeling. At the same time, after the coating surface is damaged by microcracks or shallow scratches, it can complete self-repair within 30 minutes by releasing corrosion inhibitor core material through temperature or stress triggering microcapsules. After repair, the coating's protective performance is restored. In contrast, existing nuclear power coatings have no self-healing ability, and once a small defect occurs, it continues to expand until the protective function is completely lost. The above performance breakthroughs effectively solve the industry pain points of nuclear power equipment anti-corrosion coatings being prone to failure under extreme operating conditions and requiring frequent maintenance and replacement. It can be directly adapted to the corrosion protection needs of key equipment in nuclear power plant pressurized water reactors and fourth-generation advanced reactors. Detailed Implementation

[0018] To enable those skilled in the art to understand the features and effects of the present invention, the terms and expressions used in the specification and claims are explained and defined in general below. Unless otherwise specified, all technical and scientific terms used herein have the ordinary meaning understood by those skilled in the art regarding the present invention, and in case of conflict, the definitions in this specification shall prevail.

[0019] The theories or mechanisms described and disclosed herein, whether right or wrong, should not in any way limit the scope of the invention, that is, the contents of the invention can be implemented without being limited by any particular theory or mechanism.

[0020] In this document, all features defined by numerical ranges or percentage ranges, such as numerical values, quantities, contents, and concentrations, are for the sake of brevity and convenience only. Accordingly, descriptions of numerical ranges or percentage ranges should be considered as covering and specifically disclosing all possible sub-ranges and individual numerical values ​​(including integers and fractions) within those ranges.

[0021] In this article, unless otherwise specified, the terms “contains,” “includes,” “containing,” “has,” or similar terms cover the meanings of “composed of” and “mainly composed of”. For example, “A contains a” covers the meanings of “A contains a and others” and “A contains only a”.

[0022] For the sake of brevity, not all possible combinations of the technical features in each implementation scheme or embodiment are described herein. Therefore, as long as there is no contradiction in the combination of these technical features, the technical features in each implementation scheme or embodiment can be combined arbitrarily, and all possible combinations should be considered within the scope of this specification.

[0023] This invention provides a method for preparing a high-temperature and high-pressure resistant intelligent self-healing anti-corrosion coating. It addresses the technical challenges of nuclear power equipment operating under extreme conditions such as high temperature (280~350℃ for pressurized water reactors and over 600℃ for Generation IV reactors), high pressure (15~20MPa), high humidity, and highly corrosive boric acid / seawater media. Existing metal spray coatings are prone to pore defects and lack self-healing ability, while traditional organic coatings have poor high-temperature and high-pressure resistance and cannot self-repair after aging and cracking. The invention constructs a complete and exclusive process chain from substrate pretreatment to coating curing.

[0024] The preparation method includes the following steps: S1, pretreating the surface of the nuclear power metal substrate, and then performing surface activation treatment using low-temperature plasma to obtain a pretreated substrate. The substrate can be one or more of 316L stainless steel, Incoloy 800 alloy, or Inconel 690 alloy. The pretreatment includes sandblasting to remove rust, degreasing and impurities, and deionized water cleaning. The sandblasting rust removal grade reaches Sa3.0, and the surface roughness of the substrate after sandblasting is controlled at 40~60μm to ensure the mechanical anchoring force between the coating and the substrate. After drying, surface activation modification is performed using argon low-temperature plasma with a treatment power of 300~400W and a treatment time of 5~9min. By bombarding the substrate surface with high-energy particles of low-temperature plasma, active polar groups such as hydroxyl and carboxyl groups can be introduced, while further removing adsorbed organic pollutants from the surface. This transforms the substrate surface from an inert state to a highly active state, significantly increasing the surface energy. Compared to relying solely on sandblasting for roughening, this step can significantly enhance the chemical bonding and interfacial wettability between the subsequent coating and the substrate, increasing the final coating bonding strength to over 45 MPa. This effectively solves the problem of coating delamination and peeling during long-term service.

[0025] S2, a composite film-forming matrix is ​​prepared by mixing high-temperature resistant modified epoxy resin, silicone-modified polyurethane, polytetrafluoroethylene micro powder, curing agent, dispersant, defoamer, and anhydrous ethanol solvent, followed by stirring dispersion and ultrasonic homogenization. The high-temperature resistant modified epoxy resin is at least one of silicone-modified epoxy resin, polyurethane-modified epoxy resin, or phenolic-modified epoxy resin: silicone-modified epoxy resin has low surface energy, is hydrophobic and moisture-proof, reduces internal stress in the coating, and is less prone to cracking under thermal cycling; polyurethane-modified epoxy resin significantly improves epoxy brittleness, imparting excellent impact toughness and adhesion toughness to the coating, making it less prone to cracking; phenolic-modified epoxy resin has high crosslinking density, imparting excellent resistance to strong acids, strong alkalis, salt water, and boric acid media to the coating. The curing agent is at least one of amine curing agents (such as polyamide, polyetheramine), phenolic curing agents, or acid anhydride curing agents. Amine curing agents have high crosslinking density, imparting high-temperature resistance, resistance to boric acid / acid / alkali media, and water permeability to the coating. Phenolic curing agents can achieve ultra-high crosslinking density, imparting excellent resistance to strong acids and alkalis, steam resistance, and high-temperature resistance to the coating. Acid anhydride curing agents result in high transparency, excellent dielectric properties, low shrinkage, high electrical resistance, and arc resistance in the cured product. The dispersant is at least one of polyacrylate dispersants, polyurethane-type polymeric dispersants, amine / polyamide-containing dispersants, or silicone dispersants. The defoamer is at least one of silicone defoamers, non-silicone polyether defoamers, or acrylate polymeric defoamers. The stirring and dispersion speed is 700~1000 r / min for 30~40 min, followed by ultrasonic homogenization at 200W power for 10~30 min to obtain a uniform and stable composite film-forming matrix. By using a high-temperature resistant modified epoxy resin and an organosilicon modified polyurethane as the film-forming matrix, the coating achieves high strength, high toughness, and high-temperature stability. At the same time, the introduction of polytetrafluoroethylene micropowder further reduces the surface energy of the coating and improves its anti-adhesion and chemical penetration resistance. The resulting organic-inorganic composite matrix effectively solves the problem of high-temperature aging and cracking of single resins, laying the foundation for the coating to be suitable for long-term service conditions of 400℃ high temperature and 20MPa high pressure.

[0026] S3 involves mixing high-entropy alloy nanoparticles, nano-silica aerogel, and nano-chromium oxide powder, then performing surface modification treatment with a silane coupling agent. After drying and grinding, a modified corrosion-resistant filler is obtained. Specifically, by mass percentage, the high-entropy alloy nanoparticles comprise 10-15 parts, the nano-silica aerogel 3-7 parts, and the nano-chromium oxide powder 2-4 parts; the high-entropy alloy nanoparticles used are FeCrAlTiMo high-entropy alloy nanoparticles; the silane coupling agent is KH-560; the modification temperature is 60-70℃; the modification time is 1.5-3.5h; the drying temperature is 80℃; and the particle size of the modified corrosion-resistant filler after grinding is ≤100nm. FeCrAlTiMo high-entropy alloy nanoparticles are composed of five or more main elements and possess a thermodynamically stable simple solid solution structure. In high-temperature corrosive media, they can form a dense, continuous, and self-healing three-layer composite oxide film (outer layer rich in Cr chromium oxide, inner layer rich in Al aluminum oxide, and middle layer rich in Ti / Mo oxide) through the synergistic oxidation of Cr, Al, Ti, and Mo elements, effectively blocking the inward penetration of corrosive media. The nano-silica aerogel has an ultra-high specific surface area and mesoporous structure, which can effectively adsorb corrosive ions (such as Cl-). - OH - This extends the diffusion path of corrosive media in the coating. Chromium oxide nanoparticles have extremely low solubility and excellent chemical inertness in high-temperature boric acid and seawater environments, and can be used as a passivating phase to further enhance the corrosion barrier effect of the coating. Surface modification with KH-560 silane coupling agent grafts organic functional groups onto the filler surface, improving the interfacial compatibility between inorganic nanoparticles and the organic resin matrix, preventing nanoparticle aggregation, and ensuring uniform dispersion in the coating, thereby fully leveraging the synergistic corrosion resistance of each component.

[0027] S4. Self-healing microcapsules were prepared by coating a composite core material containing corrosion inhibitors and passivators with urea-formaldehyde resin as the capsule wall material. The composite core material was composed of a molybdate corrosion inhibitor (preferably sodium molybdate) and an organic amine passivator in a mass ratio of 2:1. The capsule wall thickness of the self-healing microcapsules was controlled at 30-50 nm. These microcapsules exhibited a dual-response characteristic, triggering the release of the core material when the temperature was ≥250℃ and / or the coating microcrack stress was ≥0.5 MPa. Urea-formaldehyde resin capsules have a dense cross-linked network structure, maintaining excellent airtightness and mechanical stability during normal temperature storage and routine construction, ensuring zero leakage of the core material. However, when the coating is exposed to extreme high temperatures of ≥250℃ during service, the capsule wall material undergoes thermal softening and structural instability. Simultaneously, when the coating develops microcracks due to external forces and the stress concentration at the crack tip reaches ≥0.5MPa, the mechanical shear force generated by crack propagation directly acts on the capsule wall, causing it to rupture. These two triggering mechanisms are independent yet complementary. Temperature response ensures active slow-release protection in high-temperature environments without cracks, while stress response ensures immediate repair when mechanical damage occurs at normal or low temperatures, achieving intelligent self-healing coverage throughout the entire life cycle and service temperature range of the coating.

[0028] In step S5, the modified corrosion-resistant filler obtained in step S3 and the self-healing microcapsules obtained in step S4 are added to the composite film-forming matrix obtained in step S2. After stirring evenly and undergoing vacuum degassing, an intelligent self-healing anti-corrosion coating is obtained. The modified corrosion-resistant filler is added at 12%–18% of the total mass of the intelligent self-healing anti-corrosion coating, and the self-healing microcapsules are added at 4%–9% of the total mass of the intelligent self-healing anti-corrosion coating. This addition ratio range has been optimized: when the filler addition is below 12%, an effective passivation barrier network cannot be formed; when it is above 18%, filler agglomeration and increased coating brittleness are likely to occur. When the microcapsule addition is below 4%, the repair agent supply is insufficient and cannot completely fill cracks; when it is above 9%, it may affect the continuity, density, and mechanical strength of the coating. Vacuum degassing for 15 minutes effectively removes air bubbles introduced during stirring, preventing the formation of pore defects after the coating cures.

[0029] In step S6, a gradient spraying process is used to sequentially spray the intelligent self-healing anti-corrosion coating prepared in step S5 onto the pretreated substrate surface obtained in step S1, forming a primer layer, a mid-coat layer, and a topcoat layer, respectively. After segmented gradient temperature curing, the high-temperature and high-pressure resistant intelligent self-healing anti-corrosion coating is obtained. The primer layer has a spraying thickness of 20-30 μm and primarily serves as a strong interfacial bond with the metal substrate. The mid-coat layer has a spraying thickness of 40-50 μm and is the main functional layer supporting the corrosion-resistant fillers and microcapsules, providing the coating with anti-permeability and self-healing properties. The topcoat layer has a spraying thickness of 30-40 μm and acts as an outer protective layer, imparting hydrophobicity, erosion resistance, and radiation resistance to the coating. The total thickness of the three layers is 90-120 μm. After spraying, a segmented gradient temperature curing process is used: surface drying at room temperature for 30 minutes, pre-curing at 80℃ for 1 hour, curing at 150℃ for 2 hours, and final curing at 220℃ for 3 hours, followed by natural cooling to room temperature. Conventional coating curing methods often involve prolonged holding at a single temperature, which can easily lead to uneven internal temperature fields, rapid solvent evaporation causing porosity, and stress concentration due to curing shrinkage. This application employs a segmented gradient curing process. The 80℃ pre-curing stage allows for slow solvent evaporation and initial gelation of the coating, preventing rapid heating that could cause solvent boiling and porosity. The 150℃ curing stage promotes full cross-linking of the resin system, forming a preliminary three-dimensional network structure. The 220℃ high-temperature final curing stage drives deep cross-linking of the high-temperature resistant resin, while simultaneously allowing for sufficient relaxation and uniform release of internal stress above the glass transition temperature. This synergistic curing process significantly increases coating density and reduces porosity to below 0.8%, while effectively eliminating internal stress concentration and residual solvent porosity, preventing cracking and failure due to stress accumulation during long-term high-temperature service.

[0030] The high-temperature and high-pressure resistant intelligent self-healing anti-corrosion coating, prepared through the above multi-step synergistic process, features a microscopic phase-separated structure formed by the uniform distribution of flexible segments of silicone-modified polyurethane within a rigid epoxy network. This imparts excellent impact toughness to the coating and avoids the high-temperature embrittlement and cracking problems associated with single-resin systems. A composite filler system composed of FeCrAlTiMo high-entropy alloy nanoparticles, nano-silica aerogel, and chromium oxide forms a labyrinthine barrier effect within the coating, significantly extending the penetration path of corrosive media and synergistically generating a dense composite oxide film passivation layer in a high-temperature corrosive environment. Dual-response microcapsules are uniformly dispersed in the intermediate coating layer, forming a fully covered "intelligent repair unit network." The final coating is a multi-layered composite structure with a total thickness of 90–120 μm, a porosity ≤0.8%, and a bonding strength between the coating and the metal substrate ≥45 MPa. The coating can operate continuously for 500 hours under high temperature of 400℃ and high pressure of 20MPa without cracking, peeling or powdering. When microcracks or shallow scratches occur on the coating surface, stress concentration at the crack tip triggers the rupture of microcapsules. The released sodium molybdate and organic amine passivating agent composite core material migrate autonomously to the damaged area under capillary action. The sodium molybdate forms Fe-MoO4 on the exposed metal surface. 2- The complex precipitation film, where organic amines undergo chemical adsorption on the metal surface to form a hydrophobic corrosion-inhibiting molecular layer, works synergistically to rapidly form a dense passivation protective film in the damaged area, achieving chemical repair and restoration of protective functions in the damaged area. The entire autonomous repair process can be completed within 30 minutes, effectively solving the engineering problem of the difficulty in detecting and the continuous expansion of tiny corrosion defects in nuclear power equipment.

[0031] This invention also provides the application of the aforementioned high-temperature and high-pressure resistant intelligent self-healing anti-corrosion coating in the corrosion protection of nuclear power equipment. This coating can be widely used for corrosion protection of primary and secondary loop pipelines, steam generator heat transfer tubes, main pipeline welds, reactor pressure vessel inner walls, and high-temperature pressure-bearing equipment in generation 4 molten salt reactors and lead-cooled fast reactors. Furthermore, the preparation process of this invention is simple, parameters are controllable, and no expensive equipment is required. It enables large-scale spraying construction and is suitable for in-situ corrosion repair of both new and old nuclear power plant equipment, as well as pre-treatment for corrosion protection of newly constructed equipment, demonstrating strong engineering applicability.

[0032] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.

[0033] The following examples use instruments and equipment conventional in the art. Experimental methods in the following examples, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer. All raw materials used in the following examples are conventional commercially available products with specifications conventional in the art. In this specification and the following examples, unless otherwise specified, "%" represents weight percentage, "parts" represents parts by weight, and "ratio" represents weight proportion.

[0034] Example 1 This embodiment provides a method for preparing a high-temperature and high-pressure resistant intelligent self-healing anti-corrosion coating, including the following steps: S1, Substrate pretreatment: Select 316L stainless steel substrate, and successively perform sandblasting to remove rust to Sa3.0 level. The surface roughness of the substrate after sandblasting is 50μm. Then, degrease and remove impurities with anhydrous ethanol, clean with deionized water, and dry at 100℃. Subsequently, perform surface activation treatment with argon low-temperature plasma at a power of 300W for 5min to obtain the pretreated substrate.

[0035] S2, Preparation of composite film-forming matrix: By mass, take 48 parts of silicone-modified epoxy resin, 22 parts of silicone-modified polyurethane, 6 parts of polytetrafluoroethylene micro powder, 10 parts of polyamide curing agent, 1.5 parts of polyacrylate dispersant, 0.8 parts of silicone defoamer, and 11.7 parts of anhydrous ethanol. After mixing, stir at 900 r / min for 35 min, and then homogenize with ultrasonic at 200 W for 10 min to obtain a uniform and stable composite film-forming matrix.

[0036] S3, Preparation of modified corrosion-resistant filler: Take 10 parts of high-entropy FeCrAlTiMo nanopowder, 3 parts of nano silica aerogel, and 2.0 parts of nano chromium oxide powder, mix them, add KH-560 silane coupling agent, modify at 60℃ for 1.5h, dry at 80℃, and grind to a particle size ≤100nm to obtain modified corrosion-resistant filler.

[0037] S4, Preparation of Dual-Response Self-Healing Microcapsules: Using urea-formaldehyde resin as the capsule wall material and sodium molybdate corrosion inhibitor and organic amine passivator in a mass ratio of 2:1 as the core material, self-healing microcapsules with a particle size of 300 nm and a capsule wall thickness of 40 nm were prepared. These microcapsules have dual-response characteristics, which trigger the release of the core material when the temperature is ≥250℃ and / or the coating microcrack stress is ≥0.5 MPa.

[0038] S5, Anti-corrosion Coating Compounding: The modified corrosion-resistant filler obtained in S3 and the self-healing microcapsules obtained in S4 are sequentially added to the composite film-forming matrix obtained in S2. The amount of modified corrosion-resistant filler added is 15% of the total mass of the coating, and the amount of self-healing microcapsules added is 5% of the total mass of the coating. Stir at low speed until uniform, and degas under vacuum for 15 minutes to obtain the intelligent self-healing anti-corrosion coating.

[0039] S6, Gradient Spraying and Curing: The intelligent self-healing anti-corrosion coating prepared in S5 is applied sequentially to the surface of the pretreated substrate obtained in S1 using a gradient spraying process, forming a primer layer, an intermediate layer, and a topcoat layer, with thicknesses of 25μm, 45μm, and 35μm respectively, for a total thickness of 105μm. After spraying, the coating is allowed to dry at room temperature for 30 minutes, and then cured using a segmented gradient temperature process: pre-curing at 80℃ for 1 hour, curing at 150℃ for 2 hours, and final curing at 220℃ for 3 hours. After natural cooling to room temperature, the high-temperature and high-pressure resistant intelligent self-healing anti-corrosion coating is obtained.

[0040] S7, Performance Testing: Conventional performance tests such as bonding strength, porosity, high temperature and high pressure weather resistance, and scratch self-healing were conducted on the test pieces coated with the above-mentioned intelligent self-healing anti-corrosion coating to comprehensively evaluate the protective performance and self-healing effect of the coating under extreme working conditions.

[0041] Example 2 This embodiment provides a method for preparing a high-temperature and high-pressure resistant intelligent self-healing anti-corrosion coating, including the following steps: S1, Substrate Pretreatment: Incoloy 800 alloy substrate was selected and sandblasted to Sa3.0 grade. The surface roughness of the substrate after sandblasting was 40μm. Then, it was degreased and cleaned with anhydrous ethanol and deionized water, and dried at 100℃. Subsequently, it was surface activated by argon low-temperature plasma with a treatment power of 350W and a treatment time of 6min to obtain the pretreated substrate.

[0042] S2, Preparation of composite film-forming matrix: By mass, take 46 parts of polyurethane modified epoxy resin, 20 parts of organosilicon modified polyurethane, 8 parts of polytetrafluoroethylene micro powder, 12 parts of polyetheramine curing agent, 1.5 parts of polyurethane type polymeric dispersant, 0.8 parts of acrylate polymeric defoamer, and 11.7 parts of anhydrous ethanol. After mixing, stir at 850 r / min for 30 min, and then homogenize with ultrasonic at 200 W for 15 min to obtain a uniform and stable composite film-forming matrix.

[0043] S3, Preparation of modified corrosion-resistant filler: Take 11 parts of high-entropy FeCrAlTiMo nanopowder, 4 parts of nano silica aerogel, and 2.5 parts of nano chromium oxide powder, mix them, add KH-560 silane coupling agent, modify at 65℃ for 2h, dry at 80℃, and grind to a particle size ≤100nm to obtain modified corrosion-resistant filler.

[0044] S4, Preparation of Dual-Response Self-Healing Microcapsules: Using urea-formaldehyde resin as the capsule wall material and sodium molybdate corrosion inhibitor and organic amine passivator in a mass ratio of 2:1 as the core material, self-healing microcapsules with a particle size of 300 nm and a capsule wall thickness of 40 nm were prepared. These microcapsules have dual-response characteristics, which trigger the release of the core material when the temperature is ≥250℃ and / or the coating microcrack stress is ≥0.5 MPa.

[0045] S5, Anti-corrosion Coating Compounding: The modified corrosion-resistant filler obtained in S3 and the self-healing microcapsules obtained in S4 are sequentially added to the composite film-forming matrix obtained in S2. The amount of modified corrosion-resistant filler added is 13% of the total mass of the coating, and the amount of self-healing microcapsules added is 8% of the total mass of the coating. Stir at low speed until uniform, and degas under vacuum for 15 minutes to obtain the intelligent self-healing anti-corrosion coating.

[0046] S6, Gradient Spraying and Curing: The intelligent self-healing anti-corrosion coating prepared in S5 is applied sequentially to the surface of the pretreated substrate obtained in S1 using a gradient spraying process, forming a primer layer, a mid-coat layer, and a topcoat layer, with thicknesses of 20μm, 45μm, and 35μm respectively, for a total thickness of 100μm. After spraying, the coating is allowed to dry at room temperature for 30 minutes, and then cured using a segmented gradient temperature process: pre-curing at 80℃ for 1 hour, curing at 150℃ for 2 hours, and final curing at 220℃ for 3 hours. After natural cooling to room temperature, a high-temperature and high-pressure resistant intelligent self-healing anti-corrosion coating is obtained.

[0047] S7, Performance Testing: Conventional performance tests such as bonding strength, porosity, high temperature and high pressure weather resistance, and scratch self-healing were conducted on the test pieces coated with the above-mentioned intelligent self-healing anti-corrosion coating to comprehensively evaluate the protective performance and self-healing effect of the coating under extreme working conditions.

[0048] Example 3 This embodiment provides a method for preparing a high-temperature and high-pressure resistant intelligent self-healing anti-corrosion coating, including the following steps: S1, Substrate Pretreatment: Inconel 690 alloy substrate was selected and sandblasted to Sa3.0 grade. The surface roughness of the substrate after sandblasting was 60μm. Then, it was degreased and cleaned with anhydrous ethanol and deionized water, and dried at 100℃. Subsequently, it was surface activated by argon low-temperature plasma with a treatment power of 400W and a treatment time of 7min to obtain the pretreated substrate.

[0049] S2, Preparation of composite film-forming matrix: By mass, take 52 parts of phenolic modified epoxy resin, 18 parts of organosilicon modified polyurethane, 7 parts of polytetrafluoroethylene micro powder, 9 parts of methylcyclohexenetetraic anhydride, 1.5 parts of polyurethane polymeric dispersant, 0.8 parts of acrylate polymeric defoamer, and 11.7 parts of anhydrous ethanol. After mixing, stir at 800 r / min for 35 min, and then homogenize with ultrasonication at 200 W for 20 min to obtain a uniform and stable composite film-forming matrix.

[0050] S3, Preparation of modified corrosion-resistant filler: Take 12 parts of high-entropy FeCrAlTiMo nanopowder, 5 parts of nano silica aerogel, and 3.0 parts of nano chromium oxide powder, mix them, add KH-560 silane coupling agent, modify at 70℃ for 2.5h, dry at 80℃, and grind to a particle size ≤100nm to obtain modified corrosion-resistant filler.

[0051] S4, Preparation of Dual-Response Self-Healing Microcapsules: Using urea-formaldehyde resin as the capsule wall material and sodium molybdate corrosion inhibitor and organic amine passivator in a mass ratio of 2:1 as the core material, self-healing microcapsules with a particle size of 300 nm and a capsule wall thickness of 40 nm were prepared. These microcapsules have dual-response characteristics, which trigger the release of the core material when the temperature is ≥250℃ and / or the coating microcrack stress is ≥0.5 MPa.

[0052] S5, Anti-corrosion Coating Compounding: The modified corrosion-resistant filler obtained in S3 and the self-healing microcapsules obtained in S4 are sequentially added to the composite film-forming matrix obtained in S2. The amount of modified corrosion-resistant filler added is 16% of the total mass of the coating, and the amount of self-healing microcapsules added is 8% of the total mass of the coating. The mixture is stirred at low speed until uniform, and then vacuum degassed for 15 minutes to obtain the intelligent self-healing anti-corrosion coating.

[0053] S6, Gradient Spraying and Curing: The intelligent self-healing anti-corrosion coating prepared in S5 is applied sequentially to the surface of the pretreated substrate obtained in S1 using a gradient spraying process, forming a primer layer, a mid-coat layer, and a topcoat layer, with thicknesses of 20μm, 40μm, and 30μm respectively, for a total thickness of 90μm. After spraying, the coating is allowed to dry at room temperature for 30 minutes, and then cured using a segmented gradient temperature process: pre-curing at 80℃ for 1 hour, curing at 150℃ for 2 hours, and final curing at 220℃ for 3 hours. After natural cooling to room temperature, the high-temperature and high-pressure resistant intelligent self-healing anti-corrosion coating is obtained.

[0054] S7, Performance Testing: Conventional performance tests such as bonding strength, porosity, high temperature and high pressure weather resistance, and scratch self-healing were conducted on the test pieces coated with the above-mentioned intelligent self-healing anti-corrosion coating to comprehensively evaluate the protective performance and self-healing effect of the coating under extreme working conditions.

[0055] Example 4 This embodiment provides a method for preparing a high-temperature and high-pressure resistant intelligent self-healing anti-corrosion coating, including the following steps: S1, Substrate pretreatment: Select 316L stainless steel substrate, and successively perform sandblasting to remove rust to Sa3.0 level. The surface roughness of the substrate after sandblasting is 50μm. Then, degrease and remove impurities with anhydrous ethanol, clean with deionized water, and dry at 100℃. Subsequently, perform surface activation treatment with argon low-temperature plasma at a power of 350W for 8 minutes to obtain the pretreated substrate.

[0056] S2, Preparation of composite film-forming matrix: By mass, take 48 parts of polyurethane modified epoxy resin, 22 parts of organosilicon modified polyurethane, 8 parts of polytetrafluoroethylene micro powder, 8 parts of polyamide curing agent, 1.5 parts of amine / polyamide dispersant, 0.8 parts of organosilicon defoamer, and 11.7 parts of anhydrous ethanol. After mixing, stir at 750 r / min for 40 min, and then homogenize with ultrasonic at 200 W for 25 min to obtain a uniform and stable composite film-forming matrix.

[0057] S3, Preparation of modified corrosion-resistant filler: Take 13 parts of high-entropy FeCrAlTiMo nanopowder, 6 parts of nano silica aerogel, and 3.5 parts of nano chromium oxide powder, mix them, add KH-560 silane coupling agent, modify at 65℃ for 3h, dry at 80℃, and grind to a particle size ≤100nm to obtain modified corrosion-resistant filler.

[0058] S4, Preparation of Dual-Response Self-Healing Microcapsules: Using urea-formaldehyde resin as the capsule wall material and sodium molybdate corrosion inhibitor and organic amine passivator in a mass ratio of 2:1 as the core material, self-healing microcapsules with a particle size of 300 nm and a capsule wall thickness of 40 nm were prepared. These microcapsules have dual-response characteristics, which trigger the release of the core material when the temperature is ≥250℃ and / or the coating microcrack stress is ≥0.5 MPa.

[0059] S5, Anti-corrosion Coating Compound: The modified corrosion-resistant filler obtained in S3 and the self-healing microcapsules obtained in S4 are sequentially added to the composite film-forming matrix obtained in S2. The amount of modified corrosion-resistant filler added is 14% of the total mass of the coating, and the amount of self-healing microcapsules added is 9% of the total mass of the coating. Stir at low speed until uniform, and degas under vacuum for 15 minutes to obtain the intelligent self-healing anti-corrosion coating.

[0060] S6, Gradient Spraying and Curing: The intelligent self-healing anti-corrosion coating prepared in S5 is applied to the pretreated substrate surface obtained in S1 using a gradient spraying process to form a primer layer, a mid-coat layer, and a topcoat layer, with thicknesses of 30μm, 45μm, and 30μm respectively, for a total thickness of 105μm. After spraying, the coating is allowed to dry at room temperature for 30 minutes, and then cured using a segmented gradient temperature process: pre-curing at 80℃ for 1 hour, curing at 150℃ for 2 hours, and final curing at 220℃ for 3 hours. After natural cooling to room temperature, a high-temperature and high-pressure resistant intelligent self-healing anti-corrosion coating is obtained.

[0061] S7, Performance Testing: Conventional performance tests such as bonding strength, porosity, high temperature and high pressure weather resistance, and scratch self-healing were conducted on the test pieces coated with the above-mentioned intelligent self-healing anti-corrosion coating to comprehensively evaluate the protective performance and self-healing effect of the coating under extreme working conditions.

[0062] Example 5 This embodiment provides a method for preparing a high-temperature and high-pressure resistant intelligent self-healing anti-corrosion coating, including the following steps: S1, Substrate Pretreatment: Inconel 690 alloy substrate was selected and sandblasted to Sa3.0 grade. The surface roughness of the substrate after sandblasting was 50μm. Then, it was degreased and cleaned with anhydrous ethanol and deionized water, and dried at 100℃. Subsequently, it was surface activated by argon low-temperature plasma with a treatment power of 400W and a treatment time of 9min to obtain the pretreated substrate.

[0063] S2, Preparation of composite film-forming matrix: By mass, take 48 parts of phenolic modified epoxy resin, 20 parts of organosilicon modified polyurethane, 6 parts of polytetrafluoroethylene micro powder, 12 parts of polyetheramine curing agent, 1.5 parts of organosilicon dispersant, 0.8 parts of non-silicone polyether defoamer, and 11.7 parts of anhydrous ethanol. After mixing, stir at 700 r / min for 30 min, and then homogenize with ultrasonic at 200 W for 30 min to obtain a uniform and stable composite film-forming matrix.

[0064] S3, Preparation of modified corrosion-resistant filler: Take 14 parts of high-entropy FeCrAlTiMo nanopowder, 7 parts of nano silica aerogel, and 4.0 parts of nano chromium oxide powder, mix them, add KH-560 silane coupling agent, modify at 60℃ for 3.5h, dry at 80℃, and grind to a particle size ≤100nm to obtain modified corrosion-resistant filler.

[0065] S4, Preparation of Dual-Response Self-Healing Microcapsules: Using urea-formaldehyde resin as the capsule wall material and sodium molybdate corrosion inhibitor and organic amine passivator in a mass ratio of 2:1 as the core material, self-healing microcapsules with a particle size of 300 nm and a capsule wall thickness of 40 nm were prepared. These microcapsules have dual-response characteristics, which trigger the release of the core material when the temperature is ≥250℃ and / or the coating microcrack stress is ≥0.5 MPa.

[0066] S5, Anti-corrosion Coating Compounding: The modified corrosion-resistant filler obtained in S3 and the self-healing microcapsules obtained in S4 are sequentially added to the composite film-forming matrix obtained in S2. The amount of modified corrosion-resistant filler added is 14% of the total mass of the coating, and the amount of self-healing microcapsules added is 7% of the total mass of the coating. Stir at low speed until uniform, and degas under vacuum for 15 minutes to obtain the intelligent self-healing anti-corrosion coating.

[0067] S6, Gradient Spraying and Curing: The intelligent self-healing anti-corrosion coating prepared in S5 is applied sequentially to the surface of the pretreated substrate obtained in S1 using a gradient spraying process, forming a primer layer, a mid-coat layer, and a topcoat layer, with thicknesses of 20μm, 40μm, and 40μm respectively, for a total thickness of 100μm. After spraying, the coating is allowed to dry at room temperature for 30 minutes, and then cured using a segmented gradient temperature process: pre-curing at 80℃ for 1 hour, curing at 150℃ for 2 hours, and final curing at 220℃ for 3 hours. After natural cooling to room temperature, a high-temperature and high-pressure resistant intelligent self-healing anti-corrosion coating is obtained.

[0068] S7, Performance Testing: Conventional performance tests such as bonding strength, porosity, high temperature and high pressure weather resistance, and scratch self-healing were conducted on the test pieces coated with the above-mentioned intelligent self-healing anti-corrosion coating to comprehensively evaluate the protective performance and self-healing effect of the coating under extreme working conditions.

[0069] The intelligent self-healing anti-corrosion coatings prepared in Examples 1-5 above are dense and free of pore defects. In stress corrosion tests simulating the high-temperature and high-pressure corrosion environment of nuclear power plants, the coatings exhibit excellent corrosion resistance. After microcracks are induced by tensile stress, the dual-response microcapsules in the coating rapidly release the corrosion inhibitor core material under temperature and / or stress triggering, filling and repairing the microcracks. Ultimately, the cracks are completely closed and the coating's protective performance is fully restored, verifying the intelligent self-healing function of the coating of the present invention under extreme nuclear power conditions.

[0070] The above content is only for illustrating the technical concept of the present invention and should not be construed as limiting the scope of protection of the present invention. Any modifications made to the technical solution based on the technical concept proposed in this invention shall fall within the scope of protection of the claims of this invention.

Claims

1. A method for preparing a high-temperature and high-pressure resistant intelligent self-healing anti-corrosion coating, characterized in that, Includes the following steps: S1. The surface of the nuclear power metal substrate is pretreated, and then surface activation treatment is performed by low-temperature plasma to obtain the pretreated substrate. S2, a composite film-forming matrix is ​​prepared by mixing high-temperature resistant modified epoxy resin, organosilicon modified polyurethane, polytetrafluoroethylene micro powder, curing agent, dispersant, defoamer and anhydrous ethanol solvent, and then dispersing and homogenizing by stirring and ultrasonic treatment. S3, high-entropy alloy nanoparticles, nano-silica aerogels and nano-chromium oxide powders are mixed, and the surface is modified with a silane coupling agent. After drying and grinding, a modified corrosion-resistant filler is obtained. S4, using urea-formaldehyde resin as the capsule wall material, and coating it with a composite core material containing corrosion inhibitors and passivators, to prepare self-healing microcapsules; S5, the modified corrosion-resistant filler prepared in S3 and the self-healing microcapsules prepared in S4 are added to the composite film-forming matrix prepared in S2, and after stirring evenly and vacuum degassing treatment, an intelligent self-healing anti-corrosion coating is obtained. S6. Using a gradient spraying process, the intelligent self-healing anti-corrosion coating prepared in S5 is sequentially sprayed onto the surface of the pretreated substrate obtained in S1 to form a primer layer, a middle layer and a topcoat layer, respectively. After a segmented gradient temperature curing treatment, the high temperature and high pressure resistant intelligent self-healing anti-corrosion coating is obtained.

2. The method for preparing a high-temperature and high-pressure resistant intelligent self-healing anti-corrosion coating according to claim 1, characterized in that, In S1, the pretreatment includes sandblasting to remove rust, degreasing and cleaning, with the sandblasting grade reaching Sa3.0 and the surface roughness of the substrate after sandblasting being 40~60μm; the low-temperature plasma surface activation treatment is carried out in an argon atmosphere with a processing power of 300~400W and a processing time of 5~9min.

3. The method for preparing a high-temperature and high-pressure resistant intelligent self-healing anti-corrosion coating according to claim 1, characterized in that, In S2, the high-temperature resistant modified epoxy resin is at least one of silicone-modified epoxy resin, polyurethane-modified epoxy resin, or phenolic-modified epoxy resin; the curing agent is at least one of amine curing agent, phenolic curing agent, or acid anhydride curing agent; the dispersant is at least one of polyacrylate dispersant, polyurethane polymeric dispersant, amine / polyamide dispersant, or silicone dispersant; the defoamer is at least one of silicone defoamer, non-silicone polyether defoamer, or acrylate polymeric defoamer; the stirring and dispersion speed is 700~1000 r / min, and the stirring time is 30~40 min; the ultrasonic homogenization power is 200W, and the time is 10~30 min.

4. The method for preparing a high-temperature and high-pressure resistant intelligent self-healing anti-corrosion coating according to claim 1, characterized in that, In S3, by mass fraction, the high-entropy alloy nanopowder is 10-15 parts, the nano-silica aerogel is 3-7 parts, and the nano-chromium oxide powder is 2-4 parts; the high-entropy alloy nanopowder is FeCrAlTiMo high-entropy alloy nanopowder; the silane coupling agent is KH-560, the modification temperature is 60-70℃, the modification time is 1.5-3.5h, the drying temperature is 80℃, and the particle size of the modified corrosion-resistant filler after grinding is ≤100nm.

5. The method for preparing a high-temperature and high-pressure resistant intelligent self-healing anti-corrosion coating according to claim 1, characterized in that, In S4, the composite core material is composed of molybdate corrosion inhibitor and organic amine passivator in a mass ratio of 2:1; the self-healing microcapsule has a wall thickness of 30~50nm; the self-healing microcapsule has a dual-response characteristic of triggering the release of the core material when the temperature is ≥250℃ and / or the coating microcrack stress is ≥0.5MPa.

6. The method for preparing a high-temperature and high-pressure resistant intelligent self-healing anti-corrosion coating according to claim 1, characterized in that, In S5, the amount of modified corrosion-resistant filler added is 12% to 18% of the total mass of the intelligent self-healing anti-corrosion coating; the amount of self-healing microcapsules added is 4% to 9% of the total mass of the intelligent self-healing anti-corrosion coating.

7. The method for preparing a high-temperature and high-pressure resistant intelligent self-healing anti-corrosion coating according to claim 1, characterized in that, In S6, the thickness of the primer layer is 20~30μm, the thickness of the intermediate layer is 40~50μm, and the thickness of the topcoat layer is 30~40μm. The segmented gradient temperature curing process is as follows: surface drying at room temperature for 30min, pre-curing at 80℃ for 1h, curing at 150℃ for 2h, and final curing at 220℃ for 3h, followed by natural cooling to room temperature.

8. A high-temperature and high-pressure resistant intelligent self-healing anti-corrosion coating, characterized in that, It is prepared by any one of the preparation methods described in claims 1 to 7.

9. The high-temperature and high-pressure resistant intelligent self-healing anti-corrosion coating according to claim 8, characterized in that, The coating is a multi-layer composite structure with a total thickness of 90~120μm and a porosity of ≤0.8%. The bonding strength between the coating and the metal substrate is ≥45MPa. The coating can be continuously operated for 500 hours at 400℃ high temperature and 20MPa high pressure without cracking, peeling or powdering. Moreover, the coating surface can be self-repaired within 30 minutes after microcracks or shallow scratches occur.

10. The application of a high-temperature and high-pressure resistant intelligent self-healing anti-corrosion coating as described in claim 8 or 9 in the corrosion protection of nuclear power equipment, characterized in that, The coating is used for corrosion protection of primary and secondary loop pipes, steam generator heat transfer tubes, main pipe welds, reactor pressure vessel inner walls, and high-temperature pressure equipment in fourth-generation molten salt reactors and lead-cooled fast reactors in nuclear power plants.